Evaluation of Cloud and Precipitation Response to Aerosols in WRF‐Chem With Satellite Observations. Issue 18 (16th September 2020) - Liu, Zhoukun; Wang, Minghuai; Rosenfeld, Daniel; Zhu, Yannian; Bai, Heming; Cao, Yang; Liang, Yuan
Abstract: Large uncertainties remain in the key physical processes associated with aerosol‐cloud interactions (ACI) in models. With the help of A‐Train satellite observations, the Weather Research and Forecasting Model with chemistry (WRF‐Chem) model with two microphysical schemes, Morrison (MOR) and Lin (LIN), is evaluated by quantifying the susceptibilities of cloud properties, precipitation characteristics, and warm rain process to aerosols for marine stratocumulus over the Southeast Pacific. We reduced the meteorological control on clouds by stratifying them using cloud geometric thickness. Our results show that while the cloud fraction increases with increasing cloud droplet number concentration (Nd ) in observation and simulations, the susceptibility of cloud fraction to Nd in simulations are only half of that in the observation. The cloud liquid water path increases with Nd in simulations but decreases slightly in the observation. Compared with the observations, the warm rain in WRF‐Chem simulations is generally less suppressed by aerosols, and it initiates at a much smaller cloud droplet effective radius (Re ). The conversion from cloud to rain is substantially faster in simulations compared to satellite observations. The conversion rate accelerates at Re ≈ 13 μm in observations and at Re ≈ 9 μm in simulations. Key Points: The susceptibility of cloud fraction in WRF‐Chem simulations is only half of that in the A‐Train satellite observations The rain rate and probability in simulations are largely overestimated and less suppressed by aerosols The warm rain initiates at smaller droplet size in simulations, due to the faster conversion process